A Compact Printed End-Fire Antenna for Radio Frequency Identification (RFID) Handheld Reader - Sun, Yuanhua; Wen, Guangjun; Wang, Ping; Huang, Yongjun; Du, Zhibo (Applied Computational Electromagnetics Society Journal (ACES), 2021)
A new compact end-fire linear polarized printed antenna for a handheld radio frequency identification (RFID) reader is proposed for ultra high frequency (UHF) radio frequency identification (RFID) system in North America. The proposed planar end-fire antenna using two meandered dipole drivers, a folded reflector and a rectangular reflector are presented. The new antenna uses low-cost fabrication. The advantage of the end-fire antenna with meander dipole drivers compared to the conventional quasi-Yagi antenna is a reduction in the length of the driver, which allows closer space for RFID reader. the dimension of the antenna is 80? 59 mm2. The antenna has maximum gain of 3.6 dB and VSWR better than 2 around the US RFID bands (902- 928MHz). We describe the antenna structure and present the comparison of simulation results with experimental data. The proposed antenna is fabricated, and measured reflection coefficient, radiation patterns and gain are presented.